Charter and Ordinances of the City of La Crosse, at 202, Ordinance no. 27 (1888) - (:unkn) unknown (General Publisher, 1881)
Prohibited discharge of any cannon, gun, fowling piece, pistol, firearms, squibs, cracker, any of other thing containing powder or explosive material, or set off any fireworks. Violators fined not less than one but no more than twenty-five dollars.
--
Keywords: DISCHARGE